Kyoto's renaissance
1 online resource.
Keywords: Draws on archive of material, a first in English to take an in-depth look at Kyoto's modern transformation - its reinvention after 'collapse' (Meiji Restoration) and relocation of the imperial court to Tokyo. Includes: introduction, chapters on notable historical elements that sustain Kyoto as a quintessentially modern 'ancient capital' today.